Deformation Mechanism and Control Technology of the Surrounding Rock of the Floor Roadway under the Influence of Mining - Qingchong Zhao; Baojie Fu; Jiadi Yin (Advances in Civil Engineering)
Deformation and failure mechanism of the surrounding rock of the floor roadway under the influence of working face mining is complicated, and roadway control is difficult. The floor roadway of the 11123 working face in Pan’er Mine is taken as the research object of this study based on semi-infinite body theory of elastic mechanics to establish a mechanical model along the advancing direction of the working face and derive the stress expression of any point in the affected area of floor mining. According to the theoretical results, effective reinforcement and support schemes are then proposed. FLAC3D numerical simulation analyzes the stress and deformation of the surrounding rock of the floor roadway before and after the reinforcement. The numerical simulation results showed that (1) mining abutment pressure of the overlying working face forms a certain range of stress concentration on the roof and two sides of the roadway and will cause deformation and damage to the floor roadway and (2) overall bearing capacity of the surrounding rock of the roadway is significantly improved, and surface displacement of the floor roadway is reduced by 64 mm through the reinforcement and support of the floor roadway. On-site monitoring data of the floor roadway in the 11123 working face of Pan’er Mine showed that the maximum displacement of the roadway roof and two sides is controlled at approximately 80 mm, and the surrounding rock deformation of the roadway is appropriately controlled to meet the needs of safe production.